Effect of Background Music on Attentional Control in Older and Young Adults - Cloutier, Amélie; Fernandez, Natalia B.; Houde-Archambault, Catherine; Gosselin, Nathalie (Frontiers in Psychology, 2020)
Healthy aging can be accompanied by cognitive decline that includes diminished attentional control, an executive function allowing us to focus attention while inhibiting distractors. However, previous studies have demonstrated that background music can enhance some executive functions, in both young and older adults. According to the arousal-mood theory, the beneficial influence of background music on cognitive performance would be related to its ability to increase the arousal level of the listeners and to improve their mood. Consequently, a stimulating and pleasant music might optimally enhance attentional control. Therefore, this study aimed at determining if the influence of background music, and more specifically its arousal level, might improve attentional control in older adults and whether this effect is similar across older and young adults. To do so, older and young adults performed a flanker task under the exposition of three auditory conditions: stimulating music, relaxing music, and silence. Participants had to indicate as fast and as accurately as possible the direction of a central arrow, which was surrounded by four congruent or incongruent arrows (e.g., > > > > > or < < > < <). As expected, reaction times were slower for the incongruent compared to congruent trials. Interestingly, this difference was significantly greater under the relaxing music condition compared to other auditory conditions. This effect was the same in the two age groups. In conclusion, relaxing music seems to impair attentional control compared to stimulating music and silence, regardless of age.